Effect of Left Atrial Ablation Process and Strategy on Microemboli Formation During Irrigated Radiofrequency Catheter Ablation in an In Vivo Model. (January 2016) - Takami, Mitsuru; Lehmann, H. Immo; Parker, Kay D.; Welker, Kirk M.; Johnson, Susan B.; Packer, Douglas L.
Abstract : Background—: Formation of microemboli during catheter ablation has been suggested as a cause for asymptomatic cerebral emboli. However, it is unknown which part of the process and ablation setting/strategy is most strongly related to this occurrence. Methods and Results—: A total of 27 pigs were used. Catheter/sheath manipulations in left atrium were performed in 25 of 27 pigs outfitted with microemboli monitoring systems. Ablations using open-irrigated radiofrequency catheters were performed in 18 of 25 pigs. Two of 27 pigs did not undergo left atrial procedures and were injected with microembolic materials in the carotid artery to serve as positive controls. In total, 334 sheath/catheter manipulations (transseptal puncture, sheath flushing, catheter insertion, pulmonary vein venography, and sheath exchange) and 333 radiofrequency applications (power setting, 30/50 W; point-by-point/drag ablations) were analyzed. High microbubble volume in the extracorporeal circulation loop and a high number of microembolic signals in carotid artery were observed during sheath/catheter manipulations especially in saline/contrast injections at fast speed and ablations with steam pop. Fast sheath flushing produced significantly higher microbubble volume than slow sheath flushing (median, 12 200 versus 121 nL; P <0.0001). A total of 44 of 126 (35%) blood filters in the circulation loop showed microparticles (thrombus/coagulum and tissue). Most of them were seen after radiofrequency application especially in 50-W ablations, drag ablations, and steam pop. Brain magnetic resonance imaging showed positive-embolic lesions in control pigs. Conclusions—: Formation of microbubbles was the greatest during fast saline/contrast injections and steam pops, whereas high-power radiofrequency applications, drag ablations, and steam pops produced most of the microparticles. Abstract : Supplemental Digital Content is available in the text.